The relationship between organizational culture and employee job performance: a study on manufacturing SMEs in Penang - Gunasigren, Mogana (2021)
The aim of this research was to study the relationship of four different aspects of organizational culture, namely, working environment, teamwork, communication and reward system towards employee job performance at manufacturing SME, specifically in Penang. Despite extensive studies on organizational culture and job performance, empirical research on this subject, particularly for manufacturing SME in Penang, has been limited. 250 questionnaires were distributed to manufacturing SME's, with 232 completed questionnaires returned. To test the study hypotheses, regression models were used. The findings of this research revealed that working environment, teamwork, communication and reward system are related to employee job performance. This research contributes to a better understanding of the relationship of organizational culture and employee job performance among manufacturing SMEs in Penang state.